Signal-Detection, Threshold, and Dual-Process Models of Recognition Memory: ROCs and Conscious Recollection - Yonelinas, Andrew P.; Dobbins, Ian; Szymanski, Michael D.; Dhaliwal, Harpreet S.; King, Ling (Consciousness and cognition, 1996)
Threshold- and signal-detection-based models have dominated theorizing about recognition memory. Building upon these theoretical frameworks, we have argued for a dual-process model in which conscious recollection (a threshold process) and familiarity (a signal-detection process) contribute to memory performance. In the current paper we assessed several memory models by examining the effects of levels of processing and the number of presentations on recognition memory receiver operating characteristics (ROCs). In general, when the ROCs were plotted in probability space they exhibited an inverted U shape; however, when they were plotted inzspace they exhibited a U shape. An examination of the ROCs showed that the dual-process model could account for the observed ROCs, but that models based solely on either threshold or signal-detection processes failed to provide a sufficient account of the data. Furthermore, an examination of subjects' introspective reports using the remember/know procedure showed that subjects were aware of recollection and familiarity and were able to consistently report on their occurrence. The remember/know data were used to accurately predict the shapes of the ROCs, and estimates of recollection and familiarity derived from the ROC data mirrored the subjective reports of these processes.